When is it safe to perform abdominal transplantation in patients with prior SARS‐CoV‐2 infection: A case series. Issue 12 (7th November 2021) - Natori, Yoichiro; Anjan, Shweta; Martin, Eric F.; Selvagi, Gennaro; Villavicencio, Aasith; Coro, Ana; Mendez‐Castaner, Lumen A.; Mattiazzi, Adela; Pagan, Javier; Ortigosa‐Goggins, Mariella; Roth, David; Kupin, Warren; et al.
Abstract: Background: The Coronavirus disease 2019(COVID‐19) pandemic has negatively impacted worldwide organ transplantation. However, there is limited information on recipients transplanted after SARS‐CoV‐2 infection. A full understanding of this scenario is required, as transplantation is a life‐saving procedure and COVID‐19 remains an ongoing threat. Methods: Abdominal organ transplant recipients diagnosed with COVID‐19 prior to transplantation were identified by chart review and clinical data were collected. The primary outcome was the transplant outcome including graft loss, rejection and death, and reactivation of infection post‐transplant. Results: We identified 14 patients who received abdominal organ transplants after symptomatic PCR confirmed SARS‐CoV‐2 infection; four patients had a positive PCR at the time of admission for transplantation. The median time of follow‐up was 79 (22‐190) days. One recipient with negative PCR before transplant tested positive 9 days after transplant. One of 14 transplanted patients developed disseminated mold infection and died 86 days after transplant. During the follow‐up, only one patient developed rejection; thirteen patients had favorable graft outcomes. Conclusions: We were able to perform abdominal transplantation for patients with COVID‐19 before transplant, even with positive PCR at the time of transplant. Larger studies are needed to determine the time to safe transplant after SARS‐CoV‐2 infection.